Subandhu and Daṇḍin - Maan Singh, 1937- (Meharchand Lachhmandas, 1979)
Comparative study between two classical Sanskrit authors, with special reference to the Vāsavadattā and Avantīsundarīkathā portion of Daśakumāracarita.